2014
DOI: 10.1002/ejoc.201301854
|View full text |Cite
|
Sign up to set email alerts
|

Peptidosteroid Tweezers Revisited: DNA Binding Through an Optimised Design

Abstract: A dipodal peptidosteroid based on a deoxycholic acid scaffold was designed as a transcription factor model to study, and ultimately interfere in, selective protein–DNA interactions. In this paper, the selective binding of such a dipodal peptidosteroid to its DNA binding site is described for the first time, thus proving the concept and confirming the potential of the design. To achieve this, two 25‐mer peptides were synthesized in parallel and in close proximity on a rigid amphiphilic scaffold, attached by fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…As such, we achieved the first successful RRTR synthesis of a bivalent 13‐mer peptide conjugate. Considering its steric demands and tendencies to induce aggregation, decoration of the steroid scaffold underscores the robustness of our methodology. Within the field of peptide conjugation, the RRTR approach shortcuts the overall synthetic route, and is suitable as an alternative strategy in cases in which other assembly schemes or decoration efforts fail .…”
Section: Figurementioning
confidence: 95%
“…As such, we achieved the first successful RRTR synthesis of a bivalent 13‐mer peptide conjugate. Considering its steric demands and tendencies to induce aggregation, decoration of the steroid scaffold underscores the robustness of our methodology. Within the field of peptide conjugation, the RRTR approach shortcuts the overall synthetic route, and is suitable as an alternative strategy in cases in which other assembly schemes or decoration efforts fail .…”
Section: Figurementioning
confidence: 95%
“…Building on this successful idea of miniaturisation, Morii, Schepartz, Mascareñas Q3 and our group have enforced the proof-of-concept by using a variety of small dimerizing moieties. [7][8][9][10][11][12] Subsequently, we have shown that the attachment of the basic region peptides to a rigid scaffold, a derivative of deoxycholic acid in this case, also allows selective recognition of DNA. Indeed, our previous work on cMyc-Max b-HLH-ZIP and GCN4-bZIP proteins showed that this type of steroid-based constructs show potential for binding DNA.…”
Section: Q4mentioning
confidence: 99%
“…(d) Morii's supramolecular linker based on a β‐cyclodextrin–adamantane complex , . (e) Madder's steroid linker , . (f) Madder's cyclodextrin dimer .…”
Section: Dna‐binding Peptidesmentioning
confidence: 99%
“…Curiously, whereas the α‐cyclodextrin and β‐cyclodextrin GCN4 br dimers display rather similar binding affinities for the ATF/CREB site, with K D (α‐CD/DNA) = 50 ± 20 n m and K D (β‐CD/DNA) = 30 ± 20 n m , the γ‐cyclodextrin analogue binds with weaker affinity to the same DNA [ K D (γ‐CD/DNA) = 100 ± 60 n m ] and appears to give rise to nonspecific complexes in Electrophoretic Mobility Shift Assays (EMSAs), thus suggesting that the distance between the two GCN4 basic regions in the γ‐cyclodextrin dimer is not optimal for their simultaneous insertion as required in the specific complex . Madder's group has also reported the application of steroid scaffolds for the homodimerization of GCN4 basic regions, as well as for the heterodimerization of the basic regions of related c‐Myc/Max basic Helix–Loop–Helix transcription factors, a class of TFs related to the bZIP family, containing an additional loop between the leucine zipper and the basic region . The use of a steroidal cholic acid moiety as dimerizer element was justified, because it provides a rigid and synthetically accessible scaffold with which to attach the peptides, with reported benefits for improving the cell uptake of the conjugates (Figure e).…”
Section: Dna‐binding Peptidesmentioning
confidence: 99%